PERILAKU ANTI SOSIAL PADA ANAK SEKOLAH DASAR DAN UPAYA PEMECAHANNYA - Susan Maulani (MADROSATUNA : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2019)
Anti-social behavior does not only appear among adolescents and adults, but also appears among elementary school students. Behaviors such as bullying, aggression and violence are anti-social behaviors. Anti-social behavior in childhood and adolescence is categorized into behavioral disorders, explosive impulses, stealing, damage, physical and psychological aggression, bullying, running away from home and skipping. Education is required to be able to form humans who can get along with other humans. Humans with education are prepared to be able to adjust to any situation they face and education in elementary school is an important phase of children's development which will affect the entire development of the child including its social development. The phenomena that occur today need to be addressed immediately, so as not to have a negative impact on the development of the next child.